Endoscopic and clinicopathological features of early gastric papillary adenocarcinoma - Zuo, Zhenxiang; Qi, Xing; Cui, Xiujie; Yu, Bin; Zhang, Huimin (Frontiers in Oncology, 2024)
ObjectivesGastric papillary adenocarcinoma (GPA), a well-differentiated gastric adenocarcinoma, is associated with a worse prognosis compared to other differentiated gastric adenocarcinomas. Therefore, there is an urgent need to characterize its endoscopic manifestations for guiding biopsy site selection and achieving accurate diagnosis.MethodsFrom January 1, 2016, to December 31, 2022, the data of 46 cases of early gastric papillary adenocarcinoma (EGPA) and 183 cases of early gastric differentiated tubular adenocarcinoma (EGDTA) diagnosed via pathological examination following endoscopic submucosal dissection (ESD) at the Second Hospital of Shandong University were collected. Propensity score matching (PSM) was employed to match 92 EGDTA patients at a ratio of 1:2, serving as the control group. Differences between the two groups were analyzed using multivariable logistic regression. Lastly, the relationship between vessels within epithelial circle (VEC) structures in EGPA and the degree of malignancy was assessed.ResultsCompared with EGDTA, EGPA was more likely to infiltrate the submucosa, more frequently associated with poorly differentiated cancer components, and more prone to invading lymphatic and blood vessels. EGPA was primarily located in the lower stomach and manifested as a uniformly elevated pattern under endoscopy, while VEC structural positivity could be visualized under ME-NBI. Moreover, EGPA lesions had larger diameters and were characterized by high expression of gastric mucins, namely MUC5AC and MUC6. When EGPA infiltrated the submucosa or contained poorly differentiated cancer components, the VEC structures were smaller.ConclusionsThe present study demonstrated that EGPA exhibits a higher degree of malignancy. Endoscopic findings of a raised lesion with a uniform color under endoscopy and the presence of VEC structures under ME-NBI suggest a high possibility of EGPA. Moreover, smaller VEC structures were associated with a higher degree of malignancy, which may assist in guiding the selection of biopsy sites under endoscopy.